Beginning CSS : Cascading Style Sheets for Web Design. - York, Richard; Pouncey, Ian (Wrox programmer to programmer, 2011)
Completely updated material and new examples show you what CSS can do With the latest versions of Firefox, Safari, Internet Explorer, and other browsers released, CSS is more essential than ever. This beginner guide demonstrates how cascading style sheets can be used to define styles to items in Web pages, rather than format each item individually. Each lesson in this full-color book has been methodically revised to be more concise and efficient, making your learning experience as productive as possible. Covers the latest in CSS, including the new features of Internet Explorer, Firefox, Safari.